Avaliação do desempenho de misturas asfálticas recicladas mornas em laboratório e em campo - Oliveira, Jardel Andrade de (2013)
The paving process uses large amounts of natural resources thus requiring actions to mitigate the resulting environmental damage. Observing a road section, you can highlight activities that affect the environment, such as deforestation, mineral extraction for the production of aggregates and petroleum extraction and refining for use in asphalt layers. This activity also uses processes that generate large volumes of environmental liabilities, such as milling and demolition material. The reclaimed asphalt pavement (RAP) can be recycled and reused, for example in the production of RAP hot mixtures asphalts (HMA). The high temperatures that need to be used to produce acceptable workability of the asphalt mixtures can affect the environment and the workers on the construction site. The asphalt binder when subjected to high temperatures releases fumes known to be health hazardous. To mitigate these hazards, one can use the warm mixtures asphalt (WMA). This technology uses lower temperatures than the ones normally applied for HMA, thereby aforementioned emissions can be mitigated. It is also possible that the asphalt mixtures can be implemented with lower energy consumption. One can still use RAP WMA making use of both solutions already mentioned, RAP HMA and WMA. This work aims to use both techniques together and evaluate RAP WMA with respect to its workability, compactability and mechanical behavior. In order to achieve this objective it will be characterized in the laboratory HMAs with different RAP percentages and WMA additive. Such mixtures are also subsequently tested in the field using experimental sections. Analyzing the results it is noticed that the RAP WMAs has a promising potential since they presented the same volumetric parameters and mechanical behavior when compared to those obtained for the conventional asphalt mixtures. These parameters have been achieved without the need for changes in the equipment used for the production of these mixtures. It was possible to attain savings in binder consumption of up to 45% and conventional aggregates of up to 50%.A reduction in energy consumption is also achieved during the production of asphalt mixtures due to reductions in temperature to 40°C.